The TiO2 films with sandwich-type polyoxometalates in dye sensitized solar cells with electron recombination decreasing and dye adsorption increasing. Issue 3 (10th June 2022) - Ji, Tuo; Wu, Di; Zhang, Xiaowen; Zhao, Yue; Xu, Kaicheng
Abstract: Unfavorable electron recombination, which hinders the efficiency of dye-sensitized solar cells (DSSCs), usually occurs at the TiO2 /dye/electrolyte interface on a photoanode. Polyoxometalates (POMs), as good electron acceptors, can be used as electron-transfer materials in DSSCs to improve electron transport in TiO2 and reduce electron recombining on the interface of a photoanode. In this paper, the pure inorganic sandwich-type POM Na9 [Na3 (H2 O)6 Cu3 (H2 O)3 (SbW9 O33 )2 ]·40H2 O (Cu3 Na3 POM) was mixed with TiO2 to form nanocomposites by simple sol-gel method. X-ray photoelectron spectroscopy (XPS) proved that Cu3 Na3 POM and TiO2 combined. Then the nanocomposite was doped with P25 to form Cu3 Na3 POM@TiO2 /P25 photoanodes which were applied to the DSSCs. The Cu3 Na3 POM improved the transfer and recombination of electrons in the photoanode, proved by open circuit voltage decay (OCVD) and electrochemical impedance spectroscopy (EIS). Scanning electron microscopy (SEM) and ultraviolet-visible (UV-vis) absorption spectra showed that Cu3 Na3 POM optimized the morphology of the photoanode and the adsorption capacity of dye. The electrochemical test showed that the photoelectric conversion efficiency of DSSCs with Cu3 Na3 POM@TiO2 /P25 photoanodes was enhanced to 6.91%, which was 13.66% higher than the DSSCs without Cu3 Na3 POM. Graphical Abstract: UF0001